Analytical modeling of wireless communication systems - Chiasserini, Carla Fabiana (ISTE Ltd/John Wiley and Sons Inc., 2016)
Wireless networks represent an inexpensive and convenient way to connect to the Internet. However, despite their applications across several technologies, one challenge still remains: to understand the behavior of wireless sensor networks and assess their performance in large-scale scenarios